2012
DOI: 10.1371/journal.pgen.1003070
|View full text |Cite
|
Sign up to set email alerts
|

Insertion/Deletion Polymorphisms in the ΔNp63 Promoter Are a Risk Factor for Bladder Exstrophy Epispadias Complex

Abstract: Bladder exstrophy epispadias complex (BEEC) is a severe congenital anomaly; however, the genetic and molecular mechanisms underlying the formation of BEEC remain unclear. TP63, a member of TP53 tumor suppressor gene family, is expressed in bladder urothelium and skin over the external genitalia during mammalian development. It plays a role in bladder development. We have previously shown that p63−/− mouse embryos developed a bladder exstrophy phenotype identical to human BEEC. We hypothesised that TP63 is invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(17 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…Furthermore, a genome‐wide expression analysis independently implicated p63 as a contributing factor in the BEEC etiology (Qi et al, ). A recent study (Wilkins et al, ) independently corroborated our data (Ching et al, ) and also suggests that ΔNp63 is the dominant promoter in human tissue and its expression is significantly reduced in BEEC tissue in early bladder formation. The authors also showed that two insertion–deletion polymorphisms including a 12‐base‐pair deletion (rs6148242) and a homozygous 1bp insertion polymorphism (rs5855273) in the ΔNp63 promoter were associated with a highly increased risk for the development of nonsyndromic BEEC among Caucasians.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, a genome‐wide expression analysis independently implicated p63 as a contributing factor in the BEEC etiology (Qi et al, ). A recent study (Wilkins et al, ) independently corroborated our data (Ching et al, ) and also suggests that ΔNp63 is the dominant promoter in human tissue and its expression is significantly reduced in BEEC tissue in early bladder formation. The authors also showed that two insertion–deletion polymorphisms including a 12‐base‐pair deletion (rs6148242) and a homozygous 1bp insertion polymorphism (rs5855273) in the ΔNp63 promoter were associated with a highly increased risk for the development of nonsyndromic BEEC among Caucasians.…”
Section: Introductionsupporting
confidence: 88%
“…Recently, Wilkins et al, () reported two polymorphisms in the ΔNp63 promoter (rs6148242, rs5855273) to be strongly associated with an increased risk of BEEC among Caucasian patients. Although we found several SNPs in the p63 gene that showed altered transmission from the parents to their BEEC offspring, the results lost statistical significance after correction for multiple testing.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced parental age is also considered as a risk factor for the complex [Boyadjiev et al, 2004]. Insertion/deletion polymorphisms related to DNp63 gene have also been reported as a genetic risk factor for BEEC [Wilkins et al, 2012]. Apart from sporadic cases, CBE is listed in association with 14 entities in the London Dysmorphology Database (LMD).…”
Section: Discussionmentioning
confidence: 99%
“…An unpublished whole exome sequencing study in six CE child‐parent trios performed through the Center for Mendelian Genomics at the University of Washington did not reveal any plausible candidate genes (Keegan et al, unpublished). Additionally, the few candidate gene and genome‐wide association studies performed to date on the bladder exstrophy‐epispadias complex (BEEC)—which includes BE, PC, and CE—reported several potential candidate genes, including ISL1 (Draaken et al, ), p63 (Qi et al, ; Wilkins et al, ), and WNT3 (Reutter et al, ).…”
Section: Introductionmentioning
confidence: 99%